Pengaturan Kewenangan Kementerian Agraria/Kepala Badan Pertanahan Nasional Dalam Mekanisme Penyelesaian Sengketa Hak Atas Tanah - Kartika Dewi, Maria Seraphine (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 3 No 2 (2018), 2018)
In the provisions of Article 11 paragraph (4) PERMEN Agraria 11/2016 hasn’t clearly set about disputes and conflicts that aren’t the authority of the ministry and become the authority of other agencies. Based on the obscure  norm, the problem is formulated: (1) How’s the regulation’s scope of the Ministry of Agrarian in the settlement of land rights disputes in Article 11 paragraph (4) PERMEN Agraria 11/2016?? and (2) how’s the effect of obscure norms of Article 11 paragraph (4) on dispute settlement which isn’t the authority of the ministry?. Used normative legal research, with the approach of legislation and conceptual approach. Legal material sourced from primary, secondary and tertiary law materials. Legal material is collected by snowball system techniques and analyzing legal materials using descriptive techniques and interpretation techniques . The results of this research: (1) Disputes and conflicts that aren’t the authority of ministries are disputes and conflicts already in the realm of criminal law and other institutions which is meant by the judiciary, the Indonesian police, the judiciary of Indonesia, and the law enforcement agencies that relevant; and (2) due to the obscure norms of Article 11 paragraph (4) there’ll be a change of legal relationship, so the legal basis of the settlement mechanism isn’t based on this rule, but the Penal Code.